Avistamientos del rorcual tropical, Balaenoptera edeni (Cetacea: Balaenopteridae) y temperatura del agua, en Baja California Sur, México - Flores Ramírez, Sergio (Universidad de Costa Rica, 1997)
Prom June 1988 to Ju1y 1991, 143 cetacean boat surveys were conducted at Babia de La Paz, B.C.S. to elucidate the relation between B. edeni 's sigbting frequency, and seasonal and annual sea surface temperature (SST). SST showed significant seasonal and annual changes respectively due to the periodic entrance of tropical water masses to the area, and the intlux of oceanographic phenomena lilee El Niño and La Niña. Such events carry associated changes in productivity and food availability at the corresponding time scales. In contrast, B. edeni 's sighting frequency did not showed correspondence to such SST seasonal or annualchanges. It was evident that B. edeni 's relative abundance changed notably only during specific oceanographic. settings derived from the interaction of annual and seasonal conditions. The results do not support B. edeni 's warm water affinity, nor the species exodus out of Bahía de La Paz during the winter. According to these and other evidences, the proposed winter emigration of such population out of the Gulf of California seems improbable